(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This article delves into the critical issue of managing financial resources in enterprises operating in Uzbekistan. With a transitional economy, enterprises face a plethora of challenges, including limited access to credit, regulatory complexities, and corruption. By analyzing existing literature and practical instances, the article provides recommendations for improvements that can ameliorate these pressing issues.